Verification of the accuracy of the recent 50 years of tree growth and long‐term change in intrinsic water‐use efficiency using xylem Δ14C and δ13C in trees in an aseasonal tropical rainforest. Issue 5 (1st March 2022) - Ichie, Tomoaki; Igarashi, Shuichi; Yoshihara, Ryo; Takayama, Kanae; Kenzo, Tanaka; Niiyama, Kaoru; Zamah Shari, Nur Hajar; Hyodo, Fujio; Tayasu, Ichiro
Abstract: Growth analysis based on tree‐ring chronology is difficult in trees in aseasonal tropical rain forests, because annual growth rings may be unclear or completely absent. Fortunately, tree growth history recorded in xylem tissue is capable of providing valuable information on the responses of trees and forests to past and present environmental changes, including global warming. We have developed a new technique for aseasonal tropical forest trees which derives their growth rates from xylem Δ 14 C, and verified its accuracy. We also determined, from xylem δ 13 C, the intrinsic water‐use efficiency (iWUE) in the past 50 years. We analysed changes in xylem Δ 14 C and δ 13 C in 23 canopy trees of 12 species in 6 families growing in Pasoh Forest Reserve, Malaysia; each stem diameter at breast height (DBH) was recorded 14 times from 1969 to 2011. We found a significant positive relationship between the growth rates determined by 14 C dating and the past DBH data. On the other hand, leaf‐internal CO2 (Ci ) content did not change with increasing atmospheric CO2 (Ca ). Thus, the iWUE increased significantly over the last 50 years in all the families and species tested. This study showed that the simultaneous measurements of xylem Δ 14 C and δ 13 C could reveal a long‐term change in tree growth and iWUE during the past 50 years with high accuracy in various species and/or individuals in aseasonal tropical rainforests exhibiting high species diversity.